The Autonomous, The Universal And The Future Of Sociology. - Alatas, Syed Hussein (2006)

(untitled)
The universal concepts of sociology are those that form the basic foundation of the discipline found in all human societies and valid for all times. Examples are the concepts of sanction, class, social stratification, social mobility, group, culture, values, religion, custom and others.